Blood on the Rising sun - Haring, Douglas G. (Macrae Smith company, 1943)
The true story of life in Manila under Japanese occuption and , later, during the American libertion. The story of the fight against the Japanese waged by a Fiipino woman, her husband, and their friends and presents an aspect of the Philippine resistance that has never yet been told.